LEARN Board Game: A Game for Teaching Software Architecture Created through Design Science Research - Sousa, Tamires A. S.; Marques, Anna B. S. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Software Architecture specifies the set of decisions about the software components, their external properties and their relationships with other elements. These activities have a direct impact on the software quality, requiring architects and developers to know and to apply appropriately the architectural concepts and standards for their decision making involving the Software Architecture. Due to this, we identified a need for designing an approach that would dynamize the teaching and learning process in Software Architecture. Educational games are an alternative for teaching in several Computing areas. Therefore, this research proposes the creation and application of LEARN (LEarning software ARchitecture fundameNtals) board game, a game for teaching architectural concepts and standards in an interactive way. We created the game using the Design Science Research methodology. We evaluated the game through a case study with undergraduate students in Software Engineering, attending the Software Architecture discipline. We used a questionnaire based on the MEEGA+ model for data collection. The results show that LEARN board game has a good usability and provided a good learning experience for the students. The LEARN new version is available for adoption in Software Architecture learning.